Detection of salmonella enteritidis and salmonella typhimurium from water and animal samples in Kubah National Park, Kuching, Sarawak - Dellroy, Donny (Universiti Malaysia Sarawak (UNIMAS), 2012)
Salmonella can cause zoonotic diseases which are transmitted between human and animals. Infection of Salmonella is called salmonellosis and most infected people may develop diarrhea, abdominal cramp and nau ea. The conventional method for detecting Salmonella serovars needed 4 to 7 days for a complete diagnosis. This study is carried out to detect the presence of S. enteritidis and S. typhimurium by using rapid method, the multiplex PCR technique. The samples were collected from anal, cloacal, feces and intestine of different type of animals including bat, squirrel, mongoose and bird in Matang Wildlife Centre and Kubah National Park, Kuching, by using swab method. Moreover, samples from water and sediment from Sungai Rayu, Matang are also taken. The samples were first inoculated into an enrichment media, Luria-Bertani broth and then cultured onto three types of selective agar; Xylose-lysine-Deoxycholate (XLD), Salmonella Chromogenic Agar Base and Hektoen Enteric (HE) agar, for isolation and identification of Salmonella spp. There are 83.3% of the total isolates which were identified as presumptive Salmonella spp. Next, the DNA extraction was carried out using cell boil method. Two primer pairs which target the sefA andjliC gene of S. enteritidis and S. typhimurium respectively, were used in the multiplex PCR. The results showed that all the isolates did not possess the targeted genes, which suggest the presence of other Salmonella serovars.